2019
DOI: 10.1186/s12871-019-0810-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ancillary drugs on sevoflurane related emergence agitation in children undergoing ophthalmic surgery: a Bayesian network meta-analysis

Abstract: Background The comparative efficacy of ancillary drugs on sevoflurane related emergence agitation (EA) in children undergoing ophthalmic surgery remains controversial. Methods The databases were retrieved in an orderly manner from the dates of their establishment to October, 2018, including PubMed, The Cochrane Library and Web of Science, to collect randomized controlled trials (RCT) of different anesthetic drugs combined with sevoflurane for ophthalmic surgery. Then a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
11
1
1
Order By: Relevance
“…More prospective studies comparing the effects of different dosages of dexmedetomidine on EA are required to establish the optimal dose. Dexmedetomidine used in tonsillectomy, adenoidectomy, ophthalmologic, and orthopedic surgeries lower the EA incidence compared with saline, which is consistent with the findings of Cho et al ( 43 ), Jiao et al ( 46 ), and Tan et al ( 42 ). Tonsillectomy with or without adenoidectomy is commonly associated with throat pain and discomfort, and the EA risk associated with this procedure is up to 55.88% and may involve “a sense of suffocation” because of edema, difficulty in swallowing, and nausea.…”
Section: Discussionsupporting
confidence: 88%
“…More prospective studies comparing the effects of different dosages of dexmedetomidine on EA are required to establish the optimal dose. Dexmedetomidine used in tonsillectomy, adenoidectomy, ophthalmologic, and orthopedic surgeries lower the EA incidence compared with saline, which is consistent with the findings of Cho et al ( 43 ), Jiao et al ( 46 ), and Tan et al ( 42 ). Tonsillectomy with or without adenoidectomy is commonly associated with throat pain and discomfort, and the EA risk associated with this procedure is up to 55.88% and may involve “a sense of suffocation” because of edema, difficulty in swallowing, and nausea.…”
Section: Discussionsupporting
confidence: 88%
“…Sevoflurane is generally the preferred anesthetic agent to induce and maintain cardiac general anesthesia in children due to its rapid induction and recovery characteristics, easily controlled anesthetic depth, stable hemodynamics and minor effect on cardiac function [ 18 ] . However, in recent years, it has been shown that one of the main complications after sevoflurane anesthesia in children is emergence delirium upon awakening from general anesthesia, with a reported incidence ranging from 10% to 80%, especially in preschoolers [ 3 , 19 ] . This agitation has a variety of manifestations, including crying, excitement and delirium after awakening.…”
Section: Discussionmentioning
confidence: 99%
“…It has the advantages of rapid analepsia, little airway stimulation, and stable hemodynamics. However, the incidence of emergence delirium is as high as 40%, which affects the postoperative recovery of children, increases the difficulty of postoperative nursing and aggravates the psychological burden on children and their families [ 3 , 4 ] . Sufentanil has a strong analgesic capacity and sedative effect and lasts longer [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Third, insufficient evidence was available in the included studies for comparing the efficacy of dexmedetomidine with that of other active comparators. However, a network meta-analysis indicated that the effects of dexmedetomidine combined with sevoflurane were superior to those of ketamine, propofol, fentanyl, midazolam, sufentanil, remifentanil, and clonidine in reducing EA risk in children undergoing ophthalmic surgery [44]. Fourth, the standard postoperative management of PONV and postoperative pain varied among the included studies.…”
Section: Plos Onementioning
confidence: 99%